Pediatric sports elbow injuries - Greiwe, R. M.; Saifi, C.; Ahmad, C. S. (Clinics in Sports Medicine, 2010)
Elbow injuries in the pediatric and adolescent population represent a spectrum of pathology that can be categorized as medial tension injuries, lateral compression injuries, and posterior shear injuries. Early and accurate diagnosis can improve outcomes for both nonoperative and operative treatments. Prevention strategies are important to help reduce the increasing incidence of elbow injuries in youth athletes.